FACTORS ASSOCIATED WITH QUALITY OF LIFE AMONG HOME-BOUND OLDER ADULTS IN MUEANG CHIANG RAI DISTRICT, CHIANG RAI PROVINCE - Janpeng, Threeraphan; Buasri, Sukanya; Kaewkanta, Patcharawan; Wimonsinlapakit, Phrakhru; Vachiladilok, Phra (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This study aimed to examine the quality of life (QoL), depression levels, and the relationships between individual factors, depression, and QoL among home-bound older adults in Mueang Chiang Rai, Chiang Rai Province. The sample consisted of 186 home-bound older adults aged 60 years and over residing in Mueang Chiang Rai, Chiang Rai Province. Participants were selected using multistage random sampling. Data collection instruments included a general demographic questionnaire, the Thai version of the World Health Organization Quality of Life-BREF (WHOQOL-BREF-THAI), and the 9-Question Depression Assessment (9Q). The Cronbach’s alpha coefficients for the WHOQOL-BREF-THAI and the 9Q were .89 and .84, respectively. Data were collected between December 2024 and February 2025. Descriptive statistics were used to analyze general data, while the relationships between individual factors, depression, and QoL were using Chi-square test, Fisher’s Exact test and Pearson’s product moment correlation coefficient. The results showed that home-bound older adults had an overall QoL at a moderate level (M = 94.94, SD = 11.86). By domain, physical health (M = 24.54, SD = 3.44), psychological health (M = 21.95, SD = 3.45), and social relationships (M = 10.72, SD = 1.82) were also at moderate levels, while the environmental domain was rate as good (M = 30.43, SD = 4.51). Depression was classified as non-depressed levels (M = 2.18, SD = 2.67). Marital status, income, and depression were found to be significantly associated with overall QoL (p < .05). These findings provide valuable insights for the development of policies, health promotion strategies, and care plans to enhance the quality of life among home-bound older adults.